The role of law enforcement in emergency management and homeland security - Landahl, Mark R.; Thornton, Tonya E. (Community, environment and disaster risk management., 2021)
The Community, Environment and Disaster Risk Management series deals with a wide range of issues relating to global environmental hazards, natural and man-made disasters, and approaches to disaster risk reduction. As people and communities are the first and the most important responders to disasters and environment-related problems, this series aims to analyse critical field-based mechanisms which link community, policy and governance systems. This book examines the role and involvement of law enforcement agencies across the spectrum of homeland security and emergency management. The chapters, developed by expert practitioners and academics in the field, focus on the mission areas of mitigation and protection, prevention, preparedness, response and recovery. The introductory -- Chapter sets the stage and the following content targets structures and activities specific to each mission area of homeland security and emergency management.